Design and fabrication of a consistent knife sharpener / Nik Rafiuddin Rizki Abd Razak and Haszeme Abu Kasim - Abd Razak, Nik Rafiuddin Rizki; Abu Kasim, Haszeme (School of Mechanical Engineering, 2023)
Based on an online survey and study, the Consistent Knife Sharpener has been developed. Most survey participants agreed on the importance of using a sharp knife for safety purposes. This project aims to create a machine that uses mechanical movements to consistently sharpen knives to a razor-sharp edge. In Malaysia, a combination silicon carbide whetstone is commonly used, which has both coarse and fine grits. However, maintaining consistent angles while sharpening with an angle guide is more crucial than the type of whetstone used. With this machine, users can easily sharpen their knives and ensure their safety and well-being after use.